Integration of HIV Testing into Maternal, Newborn, and Child Health Weeks for Improved Case Finding and Linkage to Prevention of Mother-to-Child Transmission Services in Benue State, Nigeria - Akinleye, Olusoji; Dura, Gideon; de Wagt, Arjan; Davies, Abiola; Chamla, Dick (Frontiers in Public Health, 2017)
Background: In Nigeria, maternal, new-born and child health (MNCH) weeks are campaign-like events designed to accelerate progress towards millennium development goals. The authors examined whether integrating HIV testing into MNCH weeks is feasible and can lead to increased case finding and linkage to PMTCT services. Methods: A provision of HIV test and referral to PMTCT services among pregnant women attending MNCH week during the first week of December 2014 in 13 local government areas in Benue state. Demographic, past antenatal care and HIV testing information were collected using a structured questionnaire. We used routine ANC/PMTCT data from national electronic system (DHIS-2) to compare with the results obtained from MNCH week. Results: A total of 50,271 pregnant women with median age of 25 years (IQR: 21-29) were offered HIV test. 50,253 (99.96%) accepted to get HIV testing with 1063 (2.1%) testing positive. 644 (60.6%) of those with positive results were inked to PMTCT. In multivariate analysis, marital status, gestation age and those with no ANC visit during this pregnancy were associated with HIV positive test. Approximately 30% (50,253 versus 39,080) more pregnant women received HIV testing in MNCH week compared to those who received HIV testing in routine ANC services in 2013. Of the 50253 who accepted testing, 15,611 (31.1%) did not attend ANC during this pregnancy, of which 9615 (61.6%) did not have HIV test in the past. 442 (4.6%) of these 9615 tested HIV positive. Conclusion: Integration of HIV testing into MNCH weeks is feasible and improved uptake of HIV testing and linkage to PMTCT services. However the rate of HIV positivity was lower than that reported by previous studies. The findings indicate that MNCH weeks provides opportunity to reach those who do not attend ANC services for HIV care.